GAMELAN SEKATEN DAN PENYEBARAN ISLAM DI JAWA - Joko Daryanto (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2014)
The spreading of Islamic faith in Java uses many ways or methods to propagate Islamic faith. One of the medium which is support the spreading of Islam in Java is ‘Gamelan Sekaten’. It is kind of an ensemble which is played on the occasion of Muhammad’s birthday and played as long as 1 week in ‘Bangsal Pagongan’ in front of the Great Mosque Surakarta. Before Javanese people knowing and converting into Islamic faith, Javanese people have been converted into Hindu & Buddhist faith. This psychological social condition of Javanese people becomes the obstacle for the nine muslim saints, Wali Sanga, to spread Islamic faith. Sunan Kalijaga suggested using ‘gamelan’ as the attractiveness of spreading Islam. The ‘Gamelan Sekaten’ which is used as a medium of spreading Islam in Java strongly assumed that this medium has value or element of Islam. The setting of Javanese people in that time still had a strong faith toward Hindu & Buddhist faith, so it required a tool, in this case is a ‘gamelan sekaten’, to facilitate the nine muslim saints in spreading Islamic Faith. This religious proselytizing strategy which is use ‘gamelan sekaten’ as a medium appears to be very interesting & effective to gather people. Begins with feel interest to ‘gameln sekaten’, finally, Javanese people know and convert into Islam as their faith. This Islamization process, called as religious proselytizing using cultural approach.Keywords: Gamelan Sekaten, Spreading of Islamic Faith, Cultural Approach